Monocyte chemoattractant protein-1 promoter -2518 polymorphism and susceptibility to vasculitis, rheumatoid arthritis, and multiple sclerosis: A meta-analysis - Lee, Y H; Bae, S-C (Cellular and Molecular Biology, 2016)
The purpose of this study was to examine whether the monocyte chemoattractant protein-1 (MCP-1) promoter -2518 A/G polymorphism (rs1024611) is associated with susceptibility to vasculitis, rheumatoid arthritis (RA), or multiple sclerosis (MS). A meta-analysis was conducted on the association between the MCP-1 -2518 A/G polymorphism and vasculitis, RA, and MS. Fourteen studies from 13 articles, including six on vasculitis, five on RA, and three on MS, consisting of 3,038 patients and 3,545 controls were available for the meta-analysis. The meta-analysis revealed no association between the MCP-1 -2518 G allele and vasculitis (odds ratio [OR] = 0.990, 95% confidence interval [CI] = 0.749–1.309, p = 0.943). Stratification by ethnicity indicated no association between the G allele of the MCP-1 -2518 A/G polymorphism and vasculitis in Asians and Caucasians. Meta-analysis by vasculitis type revealed an association between the GG+GA genotype of the MCP-1 -2518 A/G polymorphism and Behçet's disease (BD; OR = 1.349, 95% CI = 1.013–1.796, p = 0.040). However, sensitivity analysis showed that the association was not statistically significant after removing a study that was conducted in China (OR = 1.030, 95% CI = 0.667–1.590, p = 0.895), which indicated that the association was not statistically robust. The meta-analysis revealed no association between the MCP-1 -2518 G allele and RA (OR = 0.986, 95% CI = 0.890–1.093, p = 0.793) or MS (OR = 1.281, 95% CI = 0.802–2.046, p = 0.301). Our meta-analysis demonstrates that the MCP-1 -2518 A/G polymorphism is not associated with susceptibility to vasculitis, RA, or MS.